THE EFFECT OF PROFITABILITY, INCOME DIVERSIFICATION, BANK CAPITAL, BANK EFFICIENCY ON NON PERFORMING LOAN IN THE BANKING SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2021-2023 - Yola, Yola; Imelda, Elsa (Graduate Program of Universitas Tarumanagara, 2025)
The stability of the banking sector acts as key factor in maintaining the sustainability of the financial system, bank's operating income will be greater if many customers pay loans and interest, but it will be problem if borrower cannot return the credit. This study aims to determine the effect of profitability, income diversification, bank capital, and bank efficiency on NPLs banking companies listed on the IDX 2021-2023. Total sample obtained was 30 samples of banking companies. This test uses multiple linear regression based on panel data using Eviews 12 software. The results of this study indicate the variables that have significant effect on NPL are profitability negatively and bank efficiency positively. Bank capital and income diversification variables have an insignificant relationship with NPLs. Based on the results of this study, it’s expected the company can maintain good level of profitability so that it can defend from NPLs, the company suggested to maintain the level of capital owned, carry out cost management efficiency considerately, besides that banks also advised to have other sources income as a form of diversification and not depend on one source while using careful evaluation therefore not create NPL risks. In addition, the purpose of this study also to prove influence factors that contribute to NPLs to be more consistent and expected to contribute to all academics as well practitioners regarding the results affecting NPLs and used as basis for research and banks in implementing more effective management strategies so that national financial health could maintained.